Propolis: A natural biomaterial for dental and oral healthcare - Zohaib Khurshid; Mustafa Naseem; Muhammad S Zafar; Shariq Najeeb; Sana Zohaib (Tabriz University of Medical Sciences, 2017)
The field of health has always emphasised on the use of natural products for curing diseases. There are varieties of natural products (such as silk, herbal tea, chitosan) used today in the biomedical application in treating a large array of systemic diseases. The natural product "Propolis" is a non-toxic resinous material having beneficial properties such as antimicrobial, anticancer, antifungal, antiviral and anti-inflammatory; hence gain the attention of researchers for its potential for bio-dental applications. The study aims to explore the properties and chemistry of propolis concerning biomedical and dental applications. In addition, status and scope of propolis for current and potential future in bio-dental applications have been discussed. This review gives an insight to the reader about the possible use of propolis in modern-day dentistry.